Cobalt nanoparticle supported on layered double hydroxide: Effect of nanoparticle size on catalytic hydrogen production by NaBH4 hydrolysis - Mahpudz, A. (Elsevier Ltd, 2021)
Catalytic hydrolysis of sodium borohydride (NaBH4) is a promising method to provide clean hydrogen (H2) energy for portable devices. Therefore, designing a non-noble metal catalyst that performs well in this hydrolysis is essential. Cobalt-nanoparticles (Co-NPs) supported on magnesium-aluminium layered double hydroxide (LDH) with various mean diameter were synthesized by changing concentration of cobalt-citrate anion (Co-citrate) precursor used for ion exchange with the LDH host. Then the Co-citrate intercalated LDHs were reduced with NaBH4 to form Co-NPs. Evidence of successful intercalation was shown by X-ray diffraction (XRD) and Fourier-Transform Infrared spectroscopy (FT-IR). Transmission Electron Microscope (TEM) and Scanning TEM (STEM) observations revealed that Co-NPs were in metallic state and their mean diameter increased with the concentration of Co-citrate solution. Nitrogen physisorption isotherms showed that the surface structure of LDHs transformed from non-porous to mesoporous after chemical reduction, which indicated that the Co-NPs were formed in the interlayer of LDHs. Catalytic hydrolysis of NaBH4 at 25 Â°C clarified that the catalyst synthesized from 6 mM Co-citrate solution showed the highest H2 generation rate of 4520 Â± 251 mL minâ1Â·gCoâ1, indicating the catalyst had the optimum size of Co-NP. This activity could be considered relatively higher compared to unsupported cobalt and many other supported cobalt-base catalysts previously reported. It was also clearly shown that size of Co-NPs supported on LDH could be a significant parameter as it allowed better accessibility of reactants to the active catalyst surface to obtain maximum activity. For this optimum catalyst, the activation energy was evaluated to be 56.9 kJ molâ1. Although the catalyst was able to achieve almost the same conversion when the catalyst was repeatedly tested five times under the same condition, the catalytic activity decreased gradually. Overall, it could be revealed that Co-NPs supported on LDHs have a huge potential to be used for H2 energy production. Â© 2021 Elsevier Ltd